Pembaharuan Sistem Pendidikan Di Pondok Pesantren Nurul Yaqin Ringan-Ringan (Tazakka: Jurnal Pendidikan dan Keislaman, 2023)
This study aims to look at the renewal of the Education System which consists of curriculum, educators and students at the Nurul Yaqin Ringan-ringan Islamic Boarding School. This study uses a qualitative method with a descriptive approach. Sources of data were taken through direct interviews with informants consisting of the Caliph, Pondok Leaders, Deputy Curriculum of the Pondok, Daily Management of the El Imraniyah Islamic Development Foundation and Islamic boarding school educators Nurul Yaqin Light-ringan. To strengthen the data the researchers also collected data through observation and documentation. Overall the results of the study found that, First, the Education Curriculum at the Nurul Yaqin Mil-ringan Islamic Boarding School did not experience renewal in terms of learning books and congregations, but in terms of general education underwent several changes, Second, the renewal of Educators in book learning at the Nurul Yaqin Ringan-Ringan Islamic boarding is strengthened by coaching once a month. The three students experienced renewal in terms of promotion and selection of new students, and made an agenda for santri activities that was more filled with activities of memorizing the Qur'an and the coaching of tahsin of the Qur'an for students.
Keywords: Renewal; Education System; Islamic Boarding School